2019
DOI: 10.1590/1981-52712015v43n3rb20180187ingles
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Attitudes, and Teaching about Death and Dying in the Medical School of the Federal University of Acre, Brazil

Abstract: Death is one of the major taboos of contemporary Western society and is a forbidden and avoided subject. If in the past it was a public and domestic event, nowadays it is hidden in hospitals crowded with professionals who are unprepared to deal with issues related to the end of life. This unpreparedness is a reflex of excessively technical and non-humanistic training which favors healing over caring. Therefore, it seems medical students are taught to work against death and not with it. In this context, we soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
37

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(67 citation statements)
references
References 14 publications
2
28
0
37
Order By: Relevance
“…Rapidly aging societies need a large number of medical care professionals to help human beings who are suffering from old age, sickness, and death. Medical education nowadays is full of excessive technical and non-humanistic training which favors healing over caring, 30 and this study sheds light on the future of medical humanities education.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Rapidly aging societies need a large number of medical care professionals to help human beings who are suffering from old age, sickness, and death. Medical education nowadays is full of excessive technical and non-humanistic training which favors healing over caring, 30 and this study sheds light on the future of medical humanities education.…”
Section: Discussionmentioning
confidence: 91%
“…The literature shows that as medical caregivers better understand or are more familiar with death, their attitudes toward death are more mature, 7,8 and their attitudes toward assisting patients or families in dealing with death will be better. 29,30 Because medical and nursing students who have the co n-lying experience exhibited reduced fear of death and avoidance behaviors, they would supposedly be able to adopt more open and mature attitudes toward death-related information, and then could more readily assist patients and families in dealing with death in their future careers. We also speculated that they might be better able to handle their own emotions of loss when facing the actual death of a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Every doctor, nurse, midwife, and physiotherapist will experience patient death in his work. Most people who choose a medical faculty will encounter such a situation during their studies, which is shown by the tests carried out by future doctors [( 20 ), p. 123–133; ( 5 ), p. 110; ( 6 ), p. 108; ( 18 ), p. 207–228]. These results are consistent with our study, which showed that the vast majority of nursing students meet with the death of the patient very early, and almost all participants of master's studies experienced patient death at least once.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also point out that teaching about death, dying, and caring at end of life () takes place over several meetings and is excessively theoretical, and real experiences are left unsaid [( 20 ), p. 123–133]. In 2016, it was proven that simulation could be effectively used to teach about death and dying.…”
Section: Discussionmentioning
confidence: 99%
“…Os principais aspectos discutidos pelos artigos selecionados no que tange aos impactos psicossociais da morte e do morrer na formação médica foram aqueles ligados a seus elementos biotecnicistas; a questão do sofrimento e do despreparo diante de situações de terminalidade; as dificuldades vivenciadas pelos estudantes; e a influência de crenças e experiências pessoais. Do total de 36 artigos, 13 apresentaram críticas acerca de perspectivas da graduação médica voltadas a referências preponderantemente biomédicas organicistas e que priorizavam o tradicional paradigma científico-biológico 12,21,22,24,26,31,33,37,38,40,44,46,50 . A precariedade ou inexistência da abordagem da morte e do morrer na graduação médica resultou em um conjunto de problemas que foram identificados e discutidos nos estudos.…”
Section: Formação Médica E Seus Impactos Psicossociaisunclassified